2001
DOI: 10.1029/2000rs002521
|View full text |Cite
|
Sign up to set email alerts
|

A regional GPS receiver network for monitoring equatorial scintillation and total electron content

Abstract: Abstract. A network of Global Positioning System (GPS) single-frequency (L1) receivers has been installed in Australia and Southeast Asia for the purpose of monitoring equatorial ionospheric scintillation during the current peak in solar cycle activity. Dual-frequency receivers to measure total electron content are also operating at some stations and will be described in a later paper. With respect to equatorial scintillation our long-term intention is to characterize its statistical properties and its effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…We have assumed that there is a high degree of correlation of scintillation occurrence over longitude, not only across the field of view at each site, but also over the region in general. This is validated by the results of Thomas et al (2001) and is due to the very small magnetic declination angle over the region.…”
Section: Data Processingsupporting
confidence: 71%
See 1 more Smart Citation
“…We have assumed that there is a high degree of correlation of scintillation occurrence over longitude, not only across the field of view at each site, but also over the region in general. This is validated by the results of Thomas et al (2001) and is due to the very small magnetic declination angle over the region.…”
Section: Data Processingsupporting
confidence: 71%
“…The ISMs are based on Novatel 951 GPS single frequency (L1) receivers which have been modified to process raw data sampled at 50 Hz and calculate various parameters which characterise the observed scintillation. The ISMs are stationed at 6 separate locations in the SouthEast Asian region, a detailed description of the the network is given by Thomas et al (2001). Briefly, Fig.…”
Section: Gps Scintillation Monitor Networkmentioning
confidence: 99%
“…The 6 stations of the network [ Thomas et al , 2001] monitor an extended geographic area (see Table 1). Data gathering commenced at Parepare, Pontianak and Marak Parak in December 1997, at Darwin in June 1998, at Vanimo in August 1999 and at Fang in June 2000.…”
Section: Receiver Networksupporting
confidence: 71%
“…In a modeling study of B-1B and F-15E weapons platforms, Evans (2005)demonstrated that scintillation degrades accuracy and can, if occurring in conjunction with jamming, render GPS unavailable. In the intervening years since Thomas et al (2001), more has been learned about scintillation and GPS. Thomas' original exploration and particular presentation, however, was never expanded to include other sites or years.…”
Section: Gpsscinda Stations In Thailandmentioning
confidence: 99%